Collectivisation and Decollectivisation in Hungary. Historical Problems of Landed Property During the Political Dictatorship - Kovács, Teréz; Kovács, József Ö. (Studia Historiae Oeconomicae, 2011)
In the authors' contention the category of (landed) property includes values, social-cultural meanings and social and political power relationships. Privately owned farms were eliminated in Soviet type regimes by the means of state intervention and terror since they obstructed a program of forced industrialisation and exercising power. Collectivisation became a staggering, collective event of social history that transformed structures. The practice of eliminating private forms resulted in many respects in a particular dynamics and an independent process with its own internal logic. Subsequently, this laid the foundations for the Hungarian model of agriculture where the insistence on land was replaced by concerns for earning in cash. These conditions determined the atmosphere of decollectivisation, as well. Those persons compensated who after 1992 obtained actual landed property, were unable or unwilling to work in agriculture since they were uncertain of their skills or the profitability of production in the conditions of the new market economy.